Development of Botryllus schlosseri colonial shell and Cryptosula pallasiana pearlweed in encrustation communities at the artificial substrates (the Black Sea Sevastopol Bay) - Lyudmila B. Dalyokaya (Водное хозяйство России: проблемы, технологии, управление)
Th e mass species of macro/encrustation abundance and biomass fluctuations are to be taken into account in the process of their cultivation with the purpose of obtaining biologically active substances, in order to forecast the off shore communities formation regularities and development of methods to prevent this type of biological impairment. The article discusses dynamics of precipitation and development of mass species of the macro/encrustation communities: colonial shell Botryllus schlosseri (Pallas, 1766) and btyozoans Cryptosula pallasiana (Moll, 1803) at artificial substrates of short and prolonged exposition in the apical part of the Sevastopol bay during 1979–1987 and 2011–2015 periods.